EFEKTIVITAS PENGGUNAAN MEDIA BOARD GAME TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Sakti, Hadi Gunawan; Kartiani, Baiq Sarlita (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: Based on observations made at SMKN 1 Lingsar, it was found that the learning process still uses conventional methods and modules as learning media so that student interest and learning outcomes are low. To overcome this, interesting and fun learning is applied, one of which is by using the learning media "Board game" with the hope of improving student learning outcomes.Â The purpose of this study is to determine the effectiveness of using Board Game Media in improving the learning outcomes of Class X Students in English Language Subjects at SMKN 1 Lingsar, West Lombok Regency for the 2021/2022 academic year. The data collection methods used in this study are tests as the main method, observation and documentation as complementary methods. The data analysis technique uses the t-test formula. The results of the analysis obtained a tcount value of 10.33 and a ttable value at a significant level of 0.05% = 2.056 with d.b (N-1) = 26-1 = 25 thus that the tcount value is greater than the ttable (10.33> 2.056). This means that the null hypothesis is rejected and the alternative hypothesis is accepted which reads: There is an Effectiveness of Using Board Game Media on Improving Learning Outcomes in English Subjects for Class X Students of SMKN 1 Lingsar in the 2022/2023 Academic Year. So it can be concluded that the results of this study are "Significant". Keywords: Learning Media, Board Game, Learning Outcomes.